2015
DOI: 10.1002/jps.24376
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Swelling Measurements in Pharmaceutical Powder Compacts Using Terahertz Pulsed Imaging

Abstract: Tablet dissolution is strongly affected by swelling and solvent penetration into its matrix. A terahertz-pulsed imaging (TPI) technique, in reflection mode, is introduced as a new tool to measure one-dimensional swelling and solvent ingress in flat-faced pharmaceutical compacts exposed to dissolution medium from one face of the tablet. The technique was demonstrated on three tableting excipients: hydroxypropylmethyl cellulose (HPMC), Eudragit RSPO, and lactose. Upon contact with water, HPMC initially shrinks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Of these two batches B01 disintegrated even quicker than B02 given the lower breaking force and thus larger tablet porosity. This behaviour is in good agreement with the fact that fast absorption of a fluid was observed for powder compacts that exhibit a high porosity [23, 24]. While fast fluid penetration does not directly result in the building up of the pressure, which is necessary to break the interparticulate bonds, it is a prerequisite to initiate other mechanisms like swelling of the disintegrant [25, 26].…”
Section: Resultssupporting
confidence: 80%
“…Of these two batches B01 disintegrated even quicker than B02 given the lower breaking force and thus larger tablet porosity. This behaviour is in good agreement with the fact that fast absorption of a fluid was observed for powder compacts that exhibit a high porosity [23, 24]. While fast fluid penetration does not directly result in the building up of the pressure, which is necessary to break the interparticulate bonds, it is a prerequisite to initiate other mechanisms like swelling of the disintegrant [25, 26].…”
Section: Resultssupporting
confidence: 80%
“…These key characteristics that describe the pore network structure can often be extracted sufficiently well from high-resolution three-dimensional X-ray computed microtomography (XμCT) images of porous media [76, 77], although the detectable pore sizes are often limited by the pixel size of the image and samples have to be taken from the dosage form to achieve the highest resolution (> 0.5 μm for the most commonly used commercial bench-top instruments) [78]. In addition, traditional porosimetry techniques can be employed to measure the porosity directly using liquid or gas intrusion [79, 80].…”
Section: Factors Affecting Liquid Penetrationmentioning
confidence: 99%
“…This principle enables the monitoring of the swelling and the liquid ingress as shown in Fig. 12 [77]. Yassin et al [77] demonstrated that using this technique it is possible to analyse liquid ingress and tablet swelling quantitatively.…”
Section: Quantifying Disintegration Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ix) Tablet dissolution is crucial in medication and is strongly afected by swelling and solvent penetration into its matrix. A relection mode TPI is used to measure swelling and solvent ingress in pharmaceutical compacts [80]. (x) Layer separation is a crucial defect in many bilayer tablets.…”
Section: Terahertz Spectroscopy -A Cutting Edge Technologymentioning
confidence: 99%